Early and Late Complications in the Treatment of Chronic Forms of Periodontitis - Kholboeva Nasiba Asrorovna; Sheraliyev Murodjon Sherali oʻgʻli; Mukhammadkulova Nilufar Kurbonboy qizi (American Journal of Bioscience and Clinical Integrity, 2025)
Chronic periodontitis is a pathological condition that occurs as a result of prolonged inflammation of the periodontium, the connective tissue located around the root of the tooth. With chronic periodontitis, there is a destruction of the ligaments that hold the tooth in the gum. This is accompanied by painful sensations when pressed or exposed to hot or cold food, redness and swelling of the gums. The tooth becomes mobile, which can lead to its loss. Chronic periodontitis is one of the most common complications of caries, so it is important to undergo regular preventive examinations by a dentist.